How non-participation influences in the oral proficiency development of the students from Intermediate Intensive English I courses in the foreign Language Department, at the University of El Salvador, during the semester II-2011 - Hernández Hernández, Ileana Patricia; Marcía Herrera, Rosa Arminda; Orantes Pérez, Jocelyn Marcela; Ayala, Edgar Nicolás; Ayala, Edgar Nicolás (San Salvador, El Salvador : Universidad de El Salvador, 2012)
There is a great importance in the learning of English as a second language, although it has embraced difficulties such as the lack of participation in the classroom. So that, this study rose from the need to address a problem in participating actively in class and the influence that it has in the oral proficiency. The study took the discourse theory as a base to formulate the hypothesis because the theory states that communication is treated as the matrix of linguistic knowledge. This theory says that learners discover the meaning potential of language by participating in communication . The study amplified the concept of the variables “participation and oral proficiency According to Dafne Green, participation is understood “as the act of being involved in the class. This involvement was construed by the students in two ways: an active intervention by providing either spontaneous or unsolicited contributions, such as giving opinions, answering questions, making comments, talking about a topic, participating in group discussions, reading, and asking questions; and a second type of involvement consisting in showing interest, following classes with attention, and listening to others”.
Incluye anexos.
Tesis para optar al título de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012.
Audiencia general.